PENINGKATAN KEMAMPUAN MENYELESAIKAN SOAL CERITA MATEMATIKA DENGAN MODEL POLYA DI KELAS III SEKOLAH DASAR - Suyati, Yuliana; Marzuki, Marzuki; Margiati, Margiati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study is to determine: (1) the ability of teachers to compose a learning plan of counting the number in the story using Polya model in class III SDN 09 Padagi, (2) the ability of teachers to carry out the learning work of counting the numbers in the story problem using Polya model in class III SDN 09 Padagi, (3) learning ability of counting the number in story about using Polya model in class III SDN 09 Padagi. Type of research is action research, the form is classroom action research. The study lasted for 2 cycles. Each cycle consists of planning, implementation, observation, and reflection. Subjects in the study were third grade students SDN 09 Padagi odd semester of academic year 2017/2018 with a total of 13 students consisting of 8 male students and 5 female students. Technique of data analysis in research use descriptive statistic. The instruments used in this study are the observation sheets and test results for each cycle. The results of his research that the model Polya improve the ability to solve the story problem in class III SDN 09 Padagi on the work of counting the numbers. The statement is based on the test results that increased by 51.53% from cycle I to cycle II. On the test results per cycle has increased seen from the number of students mastery both individual and classical in the cycle I and II. Keywords: Problem story, Model Polya, Mathematics.